Pengembangan Media Audio Visual Berbasis Video Untuk Meningkatkan Literasi Membaca Pada Siswa Di MIN 3 Labuhanbatu - Marcela, Raya; Nasution, Sahkholid (Cetta: Jurnal Ilmu Pendidikan, 2025)
The purpose of this study is to develop video-based audiovisual resources to help students become more proficient readers. In order to stimulate students' interest in learning, interactive visual and aural elements are combined in the produced media. Utilising the ADDIE (Analysis, Design, Development, Implementation, Evaluation) paradigm, research and development (R&D) is the research methodology used. Fourth-grade students were the subjects of the study. The study was conducted at Labuhanbatu's MIN 3. This study collected data through observation, interviews, tests, and questionnaires. Data analysis was done both quantitatively and qualitatively. On average, 82% of expert validation fell into the "very eligible" category, 90.7% of student responses fell into the "very good" category, and 85% of students' post-test results fell into the "very good" category, according to the study's findings. Consequently, it can be concluded that this video-based content is appropriate for use as a teaching tool to improve literacy in reading.